Association of weight-adjusted waist index with all-cause and cause-specific mortality among cancer survivors: a cohort study of the NHANES 1999-2018 - Li, Shi; Jin, Jing; Zhang, Wenshun; Cao, Ying; Qin, Haiyun; Wang, Jianguang; Yu, Jiaxiang; Wang, Wenping (Frontiers in Endocrinology, 2024)
Background: Obesity is becoming more widely acknowledged as a chronic illness that raises the risk of oncogenesis. This inquiry aimed to look into the correlation between cancer patient mortality and obesity, as measured by the weight-adjusted waist index (WWI). Methods: We used continuous data from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018 as the benchmark, with a follow-up validity period of December 31, 2019. First, we assessed the correlation between WWI and the all-cause and cause-specific execution of cancer sufferers using multivariable Cox proportional hazards models. Second, a smoothed curve fit was utilized to examine the relationship between WWI and both cause-specific and all-cause mortality in cancer patients. Lastly, we analyzed the relationship between WWI and both cause-specific and all-cause mortality in cancer patients, to find out if this link held across the population subgroup evaluation and impact analyses were used as well during the last step. Results: With a median follow-up of 87.8 months, 1,547 (34.7%) of the 4,463 cancer patients had deceased. Among them, 508 (11.4%) succumbed to cancer, while 322 (7.2%) passed away due to cardiovascular disease. Multivariate Cox proportional hazards model of mortality among cancer patients revealed an all-cause mortality hazard ratio [HR=1.13; 95% CI (1.04, 1.23)] and cardiovascular mortality [HR=1.39; 95% CI (1.16, 1.67)]. Furthermore, for each unit increase in WWI, all-cause mortality was significantly higher in male cancer survivors than in female cancer survivors. Conclusions: Our study reveals substantial correlations between WWI and all-cause and cardiovascular mortality in US cancer survivors, helping to identify cancer survivors at higher risk of death and thus potentially guiding targeted interventions.